Concepts toward directing human astroplasticity to promote neuroregeneration. Issue 1 (6th September 2018) - Patel, Rajan; Muir, Matthew; Cvetkovic, Caroline; Krencik, Robert
Abstract: Astrocytes exhibit dynamic and complex reactions to various insults. Recently, investigations into the transitions that occur during cellular specification, differentiation, maturation, and disease responses have provided insights into understanding the mechanisms that underlie these altered states of reactivity and function. Here we summarize current concepts in how astrocyte state transitions, termed astroplasticity, are regulated, as well as how this affects neural circuit function through extracellular signaling. We postulate that a promising future approach toward enhancing functional repair after injury and disease would be to steer astrocytes away from an inhibitory response and toward one that is beneficial to neuroplasticity and neuroregeneration. Toward this goal, we discuss emerging biotechnological advancements, with a focus on human pluripotent stem cell bioengineering, which has high potential for effective manipulation and control of astroplasticity. Highlights include innovations in cellular transdifferentiation techniques, nanomedicine, organoid and three‐dimensional (3D) spheroid microcircuit development, and the use of biomaterials to influence the extracellular environment. Current barriers and future applications are also summarized in order to augment the design of future preclinical trials aimed toward astrocyte‐targeted neuroregeneration with a concept termed astrocellular therapeutics. Developmental Dynamics 248:21–33, 2019. © 2018 Wiley Periodicals, Inc. Key Findings: Current conceptions about astrocyte plasticity are reviewed. Emerging technologies are explored in regards to modeling and manipulating human astrocytes. Remaining unknowns and barriers in the field are emphasized.